Analisis Kedisiplinan PNS yang Berdampak Pada Pemotongan TPP Prestasi Kerja Berdasarkan Peraturan Gubernur Jawa Timur Nomor 55 Tahun 2022 Tentang Pedoman Kerja dan Pelaksanaan Tugas Pemerintahan Provinsi Jawa Timur (Studi Pada Inspektorat Provinsi Jatim) - Arsela, Tina Dwi; Gamaputra, Gading (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The Work Performance TPP policy is given as an effort to improve employee performance, improve discipline, improve employee welfare. This study aims to analyze and describe the TPP problem of Work Performance Based on Discipline. This study used a descriptive qualitative method. For the focus of the research, it used East Java Governor Regulation Number 55 of 2022 concerning Work Guidelines and Implementation of Tasks of the East Java Provincial Government. The results of research in the field show that on the indicator of employees who arrive late and go home early so that it is not in accordance with working hours, it turns out that in practice there are still employees who are late so that deductions are made. On the indicator the employee does not fill in the attendance list or does not take attendance because he forgets, takes leave or is on a business trip. In implementing this policy which is supported by the East Java Presence application, it turns out that there are still employees who forget to be absent from coming and forget to be absent from going home for various reasons so that they will receive deductions. On the indicator of employees not carrying out flag ceremonies on national and regional holidays it turns out that there are still employees who do not carry out ceremonies but the number is small and if they do not record attendance they will be subject to deductions. On the indicator of employees who do not take part in physical fitness exercises, the Inspectorate agency in 2022 will not carry out gymnastic activities with limited space. On the indicator employees are required to report late and do not report LHKPN and LHKASN have been going well. Keywords: PNS Management, TPP Work Performance, Work Discipline